(untitled) (Research, Society and Development, 2019)
Beef is one of the main foods consumed and marketed in Brazil, requiring proper quality control. Given this fact, the present study, through microbiological analysis, aimed to identify the presence of Salmonella spp. in ground beef sold in the municipalities of Vale do Guaribas in the state of Piauí. For this, 50 samples of ground beef were collected from public markets and butchers. The results obtained were compared with current legislation and classified as own or improper for consumption. It was found that of the 15 municipalities where collections were made, 93.33% had some sample not in accordance with the standard required by resolution and of the 50 samples, 84% were positive for the bacterium in question, being unfit for consumption. Incompatible hygiene practices were detected in the study and better and more effective enforcement of perishable food commercialization was necessary, overseeing critical control points and thus ensuring the provision of safe food.